(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article investigates the representation of modality in literary compositions and the linguistic strategies utilized by writers for its proficient communication. By scrutinizing a range of literary texts, this research delves into the utilization of grammatical elements, including modal verbs, adverbs, and adjectives, to articulate various levels of assurance, potentiality, compulsion, and authorization. The research approach encompasses a qualitative examination of chosen literary works aimed at discerning recurrent structures and tactics in the portrayal of modality. The outcomes illuminate the multifaceted techniques authors employ to evoke diverse modal interpretations, thereby enriching the depth and intricacy of literary discourse.